Claustrum damage and refractory status epilepticus following febrile illness. (6th October 2015) - Meletti, Stefano; Slonkova, Jana; Mareckova, Iva; Monti, Giulia; Specchio, Nicola; Hon, Petr; Giovannini, Giada; Marcian, Vaclav; Chiari, Annalisa; Krupa, Petr; Pietrafusa, Nicola; Berankova, Dagmar; et al.
Abstract : Objective: To characterize the clinical, EEG, and brain imaging findings in an adult case series of patients with de novo refractory status epilepticus (SE) occurring after a febrile illness. Methods: A retrospective study (2010–2013) was undertaken with the following inclusion criteria: (1) previously healthy adults with refractory SE; (2) seizure onset 0–21 days after a febrile illness; (3) lacking evidence of infectious agents in CSF; (4) no history of seizures (febrile or afebrile) or previous or concomitant neurologic disorder. Results: Among 155 refractory SE cases observed in the study period, 6 patients (17–35 years old) fulfilled the inclusion criteria. Confusion and stupor were the most common symptoms at disease onset, followed after a few days by acute repeated seizures that were uncountable in all but one. Seizures consisted of focal motor/myoclonic phenomena with subsequent generalization. Antiepileptic drugs failed in every patient to control seizures, with all participants requiring intensive care unit admission. Barbiturate coma with burst-suppression pattern was applied in 4 out of 6 patients for 5–14 days. One participant died in the acute phase. In each patient, we observed a reversible bilateral claustrum MRI hyperintensity on T2-weighted sequences, without restricted diffusion, time-related with SE. All patients had negative multiple neural antibodies testing. Four out of 5 surviving patients developed chronic epilepsy. Conclusions: This is a hypothesis-generating study of a preliminary nature supporting the role of the claustrum in postfebrile de novo SE; future prospective studies are needed to delineate the specificity of this condition, its pathogenesis, and the etiology.